2012
DOI: 10.1371/journal.pone.0046420
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Root-Associated Microorganisms and Peach Replant Disease Symptoms in a California Soil

Abstract: BackgroundReplant disease often occurs when certain crops are “replanted” in a soil that had previously supported the same or similar plant species. This disease typically leads to reductions in plant growth, crop yields, and production duration, and its etiology remains ill-defined. The objective of this study was to identify microorganisms associated with peach replant disease symptoms at a field location in California, USA. Soil samples were subjected to treatments to create various levels of replant diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 56 publications
4
51
1
Order By: Relevance
“…HH01 (Lee et al 2012;Hornung et al 2013). In addition, Yang et al (2012) found that Xanthomonadaceae is one of the dominant taxa exhibiting a positive association with plant weights and suggested a possible beneficial role of this group in plant growth promotion. Deep taxonomic analyses of our results revealed that Janthinobacterium in the cotton rhizosphere was significantly lower in monocropped than control soil.…”
Section: Discussionmentioning
confidence: 98%
“…HH01 (Lee et al 2012;Hornung et al 2013). In addition, Yang et al (2012) found that Xanthomonadaceae is one of the dominant taxa exhibiting a positive association with plant weights and suggested a possible beneficial role of this group in plant growth promotion. Deep taxonomic analyses of our results revealed that Janthinobacterium in the cotton rhizosphere was significantly lower in monocropped than control soil.…”
Section: Discussionmentioning
confidence: 98%
“…Because of its specific action with no serious side effects and low price, R. glutinosa is one of the popular medicines used in traditional Chinese clinical practice (Wen et al 2002;Du et al 2009;Sun et al 2012;Wang et al 2013). However, its productivity declines significantly when it is grown on a field where the preceding crop was the same (Zhao and Chen, 1991;Yu and Yang, 1994), a syndrome described as ''replanting or continuous monoculture disease''; in this, a plant species inhibits the growth of its own kind through the release of toxic chemicals into the environment (Mazzola and Manici 2012;Yang et al 2012). Replanting disease was recognized as a major problem as early as 300 BCE in various plant species such as vegetables, medicinal plants, plantation crops and horticultural crops (Zhao and Chen 1991;Zhang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrosequencing techniques are capable of providing a more comprehensive picture of all microbes present in a sample, including low-abundance species (La Duc et al 2012). The technique has been used in numerous studies to investigate bacterial communities in soils (Uhlik et al 2013;Xiong et al 2014;Yang et al 2012;Zhang et al 2013), and recently, a study focusing on bacterial communities using high-throughput sequencing to investigating ARD soils in China was published (Sun et al 2014a). However, to our knowledge, no studies exist in which both the bacterial and fungal communities of soils affected by ARD have been investigated by high-throughput sequencing.…”
mentioning
confidence: 99%